Bracketed Radioactive Seed Localization for Breast Conservation Surgery. Issue 2 (February 2020) - Dixon, Jordan; Jasra, Bharti; Ankola, Anita; Sharma, Smita; Letter, Haley
We aimed to evaluate the surgical margin outcomes and re-excision rates in patients undergoing bracketed seed localization of biopsy-proven breast cancer detected on screening mammogram. After approval by our Institutional Review Board, we retrospectively identified patients who had undergone iodine-125 seed localized lumpectomy at our institution from January 2010 to June 2017 by one of two fellowship-trained breast surgeons. Of those patients, a subset of 25 patients were identified who had undergone bracketed seed localization, defined as two or more seeds used to delineate the radiographic borders of the area of concern. All patients had originally presented with calcifications identified on screening mammogram that were subsequently diagnosed as ductal carcinoma in situ and/or invasive ductal carcinoma by image-guided biopsy performed at our institution. Eight patients had one positive margin on final surgical pathology and required re-excision (32%). One patient was converted to mastectomy. Of the patients requiring re-excision, the average maximum linear extent of calcifications was 3.4 cm (SD 0.97), whereas it was 3.1 cm (SD 1.2) in patients with negative surgical margins ( P = 0.5). Bracketing calcifications with radioactive seeds can potentially allow more patients to undergo breast conservation surgery.